2022
DOI: 10.1002/prp2.996
|View full text |Cite
|
Sign up to set email alerts
|

Toward a big picture of COVID‐19

Abstract: The paper aims to illustrate and explain the problems and opportunities for improvement in Covid management that become evident when taking a systems perspective. Critical time delays occurred in the regulation of the pandemic that the management cycle of political cybernetics makes explicit. In general, the executive management of the pandemic in global, regional, and national organizations was unprepared in detecting and responding to the onset of the waves and making appropriate decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The COVID-19 pandemic has also demonstrated that developed countries, despite their higher wealth, are not necessarily more resilient than developing countries [13,14]. Even several Western countries with advanced healthcare systems, such as France, England, Spain, Italy, and the United States, struggled to manage the pandemic, leading to many confirmed cases [15][16][17]. The impact of the pandemic is complex, posing distinctive challenges in its handling [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 pandemic has also demonstrated that developed countries, despite their higher wealth, are not necessarily more resilient than developing countries [13,14]. Even several Western countries with advanced healthcare systems, such as France, England, Spain, Italy, and the United States, struggled to manage the pandemic, leading to many confirmed cases [15][16][17]. The impact of the pandemic is complex, posing distinctive challenges in its handling [18].…”
Section: Introductionmentioning
confidence: 99%
“…Sustainability 2023, 15, x FOR PEER REVIEW 2 of 16 and integrated policy management responses to health emergencies and their impacts [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has also demonstrated that developed countries, despite their higher wealth, are not necessarily more resilient than developing countries [13,14]. Even several Western countries with advanced healthcare systems, such as France, England, Spain, Italy, and the United States, have struggled to manage the pandemic, leading to many confirmed cases [15][16][17]. The impact of the pandemic is complex, posing distinctive challenges in its handling [18].…”
Section: Introductionmentioning
confidence: 99%
“…This papers advocates for participatory design to protect the commons, 1 learns from the lessons taught by Covid (Tretter et al, 2022) and discusses community engagement inspired by President Jokowi's mission to support social enterprises. Our approach is to support One Village-Many Enterprises to progress a regenerative circular green economy in Tarumajaya, West Java.…”
Section: Introductionmentioning
confidence: 99%